Towards a better understanding of human iNKT cell subpopulations for improved clinical outcomes - Look, Alex; Burns, Daniel; Tews, Ivo; Roghanian, Ali; Mansour, Salah (Frontiers in Immunology, 2023)
Invariant natural killer T (iNKT) cells are a unique T lymphocyte population expressing semi-invariant T cell receptors (TCRs) that recognise lipid antigens presented by CD1d. iNKT cells exhibit potent anti-tumour activity through direct killing mechanisms and indirectly through triggering the activation of other anti-tumour immune cells. Because of their ability to induce potent anti-tumour responses, particularly when activated by the strong iNKT agonist αGalCer, they have been the subject of intense research to harness iNKT cell-targeted immunotherapies for cancer treatment. However, despite potent anti-tumour efficacy in pre-clinical models, the translation of iNKT cell immunotherapy into human cancer patients has been less successful. This review provides an overview of iNKT cell biology and why they are of interest within the context of cancer immunology. We focus on the iNKT anti-tumour response, the seminal studies that first reported iNKT cytotoxicity, their anti-tumour mechanisms, and the various described subsets within the iNKT cell repertoire. Finally, we discuss several barriers to the successful utilisation of iNKT cells in human cancer immunotherapy, what is required for a better understanding of human iNKTs and the future perspectives facilitating their exploitation for improved clinical outcomes.